Comprehensive improvement of induced ruminal acidosis in lambs: targeted microencapsulated essential oils and marine algae restore rumen function, systemic health, immunity, and welfare - Asmaa T. Y. Kishawy; Eman Metwally; Ioan Pet; Ghadeer A. Attia; Fayza A. Ahmed; Hala Saed; Heba Moharam; Asmaa S. Mohammed; Mirela Ahmadi; Gabi Dumitrescu; Zainab F. Helal; Ahmed Abdelfattah-Hassan; et al. (Frontiers in Veterinary Science, 2026)
This investigation was performed to evaluate the efficacy of a microencapsulated essential oils (MEOs) blend and marine calcareous algae (Marine Cal-Algae) to counteract experimentally induced ruminal acidosis (RA) in lambs by evaluating animal performance, hematological indices, general health condition, inflammatory markers, rumen fermentation milieu, and animal behavior. This study was performed on 45 yearling rams weighing 30–35 kg, randomly assigned to five experimental groups (nine lambs/group with three replicates for each), as follows: a control (healthy lambs) group and four induced RA groups. These included an untreated RA group and three treated groups receiving either essential oils (MEOs), marine calcareous algae, or a combination of both treatments. All treatment regimens lasted for 6 days after RA induction. The results revealed that skin turgor, blood capillary refill time, respiratory and pulse rates were significantly increased, while ruminal motility was significantly reduced after RA induction. Notably, the combined MEOs–marine calcareous algae treatment restored these parameters, markedly lowering skin turgor, capillary refill time, and respiratory and pulse rates while improving ruminal motility to near-control values. In addition, RA reduced lysozyme and myeloperoxidase (MPO) values, while nitric oxide (NO), C-reactive protein (CRP), and interleukin-6 (IL-6) were significantly increased. Conversely, treatment with both MEOs and marine calcareous algae mitigated these effects. Lactic acidosis decreased rumen pH, protozoa activity, and acetate:propionate ratio but increased lactate and total volatile fatty acids (TVFAs), while dual MEO-marine algae treatment reversed these shifts. Stress responses in the open field test (OFT) escalated post-acidosis (↑escapes, beats, latency; ↓exploratory sniffing), indicating heightened anxiety that was substantially attenuated by MEOs-marine algae intervention. Therefore, MEOs and marine calcareous algae supplementation can help veterinarians treat lambs with RA and promote faster recovery through natural interventions.